Challenges in rehabilitation during COVID-19 pandemic - Ceravolo, Maria Gabriella (Rehabilitacija (Ljubljana), 2021)
At least half of the survivors after SARS-CoV-2-caused disease suffer from a mild to severe deconditioning syndrome, fatigue, muscle wasting and pain, dizziness, very low tolerance to minimal efforts, depression and anxiety, or even from post-critical neurological syndrome and peripheral neuropathies. Rehabilitation changes according to the disease phase. The COVID-19 pandemic has severely hampered outpatient and home-based care, so many experts have suggested telerehabilitation as a possible solution. Fort this purpose, we established a publicly accessible web platform in March 2020 with an original therapeutic education program in Italian and English. The platform is intended for the patients discharged home after hospitalisation due to coronavirus disease, patients in isolation at home because of COVID-19 infection, and health care professionals. The platform monitors the number of visits and page views, and includes a user-satisfaction questionnaire. We have recorded 220 visitors and 623 page views, mostly during the first phase of the epidemic until the end of May 2020. The questionnaire was filled in by 50 persons; their mainly reported reduced symptoms and improved health after following the therapeutic program, and satisfaction with the offered contents. Hence, we believe that telerehabilitation is appreciated, safe and possibly useful for patients after coronavirus disease.
Keywords: COVID-19; Rehabilitation; telemonitoring; telerehabilitacija; telerehabilitation